Progressão da parturição e intervalo entre nascimentos num contexto de declínio da fecundidade: uma aplicação a países da América Latina - Gabriela Marise de Oliveira Bonifacio (2011)
The analysis of fertility decline in a population may be achieved by decomposing intrinsic aspects to it, for example, the parity, according to order, and the interval or spacing between births. Both aspects, which have been little explored in Latin American context, are indispensable tools to better understand the change in reproductive behavior, marked by the reduction of family size. This change, however, does not occur synchronously and homogeneously in the region, since countries have begun the process of fertility decline in specific times and with different paces, besides the fact that such fertility transition is markedly distinguished by socioeconomic characteristics. This occurs, for instance, in Brazil, Bolivia and Colombia. In this sense, the objective of this dissertation is to analyze the parity progression ratios and the interval between births for recent periods, in order to capture the behavior of these measures and their possible changes in the different scenarios these countries present. Thus, it will use the data on birth history cohorts of women who had completed their reproductive cycle at the time of the interview.